Analisis Sistem Informasi Akuntansi sebagai Alat Pengendalian Internal pada Penggunaan Dana BOS SDIT An-Nisa - Harahap, Muhammad Fadli; Sugianto, Sugianto (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2024)
This study aims to analyze the role of accounting information systems as an internal control tool in the management of School Operational Assistance (BOS) funds at SDIT An-Nisa. In this study, a qualitative approach was used to gain an in-depth understanding of how accounting information systems can support transparency and accountability in the use of BOS funds. Data was collected through interviews with related parties, direct observation, and documentation studies, then analyzed to identify the strengths and weaknesses of existing internal controls. The results showed that the accounting information system implemented helped in minimizing the risk of misuse of funds, although there were some aspects that needed to be improved to increase efficiency and accuracy. The findings are expected to serve as a reference for educational institutions in strengthening internal controls to optimize the use of BOS funds.